2013
DOI: 10.1111/evj.12161
|View full text |Cite
|
Sign up to set email alerts
|

The effect of insertional suspensory branch desmitis on racing performance in juvenile Thoroughbred racehorses

Abstract: JISBI causes decreased racing ability as a 2-year-old. Mild cases perform similarly to controls by their 3-year-old season, but more severe cases demonstrate reduced ability as a 3-year-old, with an increased likelihood of reinjury. Although the wastage was higher in case horses with JISBI, individual cases that make it to a race have similar earnings per start as their controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
59
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(70 citation statements)
references
References 15 publications
9
59
2
Order By: Relevance
“…In this population of 50 Thoroughbred (TB) yearlings, 66% demonstrated some degree of sesamoiditis. This finding is consistent with other studies that have shown sesamoiditis to be a common condition .…”
Section: Discussionsupporting
confidence: 93%
“…In this population of 50 Thoroughbred (TB) yearlings, 66% demonstrated some degree of sesamoiditis. This finding is consistent with other studies that have shown sesamoiditis to be a common condition .…”
Section: Discussionsupporting
confidence: 93%
“…Although it has been suggested that some horses with clinical signs of SLB desmitis have no ultrasonographic evidence of fibre disruption , in most cases this is pivotal to lesion identification . In the cases reported, four abnormalities, increased cross sectional area, a defect in the palmar/plantar abaxial margin, extrusion of disrupted ligament fibres and adjacent layered echogenic tissue, were consistent features.…”
Section: Discussionmentioning
confidence: 81%
“…In one report a degree of objectivity was introduced for juvenile injuries in Thoroughbreds. The study demonstrated that horses with juvenile SLB lesions raced significantly less as 2-and 3-year-olds (27 and 62% respectively) compared with unaffected horses (58 and 82%) [1]. This paper reports a subgroup of SLB injuries with a consistent, abaxial marginal location and their treatment by surgical removal of the disrupted tissue.…”
Section: Introductionmentioning
confidence: 82%
“…A recent study of the effects of SLB injury on the racing careers of juvenile Thoroughbreds demonstrated that horses with SLB injury started fewer races in both their 2-and 3-year-old seasons than those without [3]. Horses with mild SLB injuries performed similarly to sibling controls (those without SLB injury) in their 3-year-old seasons, but moderate to severe SLB injuries resulted in reduced performance and increased risk for re-injury.…”
Section: Introductionmentioning
confidence: 99%